STUDI KOMPARATIF PENGELOLAAN PENERIMAAN PESERTA DIDIK BARU BERBASIS GERAKAN TRANSISI PAUD KE SD YANG MENYENANGKAN - Novita Dwi Kesuma; Somantri , Manap (UNIVERSITAS BENGKULU, 2025)
The purpose of the study is to describe the conditions: the admission system fornew students, the implementation of the introduction period to the schoolenvironment and the placement of new students at SD Negeri 48 and 58Lubuklinggau. The research uses a descriptive qualitative method through datacollection techniques in the form of interviews, observations, anddocumentation. The research subjects are principals, teachers and parents ofstudents. The results of the study showed; The PPDB system has eliminated thecalistung test, the accuracy of schools determining the path and quota of studygroups and the implementation of an integrated web in the registration process.SD Negeri 48 Lubuklinggau has not yet socialized the flow, requirements andguidelines of PPDB through various media; In MPLS, there is minimal activeparticipation of parents/guardians; The placement of students in the classroomuses an integration function (age, gender or registration order).